The Optimization of Polyvinyl Alcohol and Stearic Acid in Citronella EssentialOil (Cymbopogon nardus L. Rendle) Paper Soap Formula as An Antibacterial for Staphylococcus aureus - Sumule, Arsiaty; Endang Diyah Ikasari; Cahyani, Intan Martha; Vitara, Dea (Pharmaceutical Journal of Indonesia, 2026)
Introduction: Hands that look clean can be a medium for transmitting germs. Therefore, one of the prevention efforts that can be done is diligently washing hands using soap and running water, so that practical soap preparations such as paper soap are needed. The high content of terpenoid compounds and strong antibacterial activity in citronella essential oil (Cymbopogon nardus L. Rendle) has the potential to be developed in paper soap preparations. The paper soap formulation of citronella essential oil was prepared using a combination of PVA and stearic acid. Objective: This study aims to determine the effect of the using PVA and stearic acid on physical characteristics in the citronella essential oil paper soap and determine the ratio of the concentrations of PVA and stearic acid in the optimum formula using the Simplex Lattice Design method. Methods: Paper soap formula optimization analyzed by Simplex Lattice Design method using Design Expert 10.0.1. Optimized parameters were pH, foam stability, free alkali, tensile strength, and percentage elongation. The optimum formula was tested for antibacterial activity of Staphylococcus aureus. Results: The results of Design Expert 10.0.1 showed that the optimum formula with a concentration ratio of PVA was 5.113% and stearic acid was 2.387%. The experimental results obtained an average of pH 10.95; foam stability 90.66%; free alkali 0.08%; tensile strength 0.7185 N/m2; and percentage elongation 15.12%. The results of the one sample T-test showed that these observations are differed not significantly to the result of the predictions indicating that the equation of each optimization parameter was valid except for the percentage elongation. The optimum formula has antibacterial activity of Staphylococcus aureus with a diameter of 8.52 mm. Conclusion: PVA and stearic acid have a significant effect on optimization response.